2018
DOI: 10.1155/2018/8571530
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Country‐of‐Origin Effect, Culture, and Type of Product with the Consumer’s Shopping Intention: An Analysis for Small‐ and Medium‐Sized Enterprises

Abstract: To obtain information about foreign markets is a very complex task for small- and medium-sized enterprises. This work’s aim is to find out how certain variables are related to the consumer’s shopping intention. It will help these firms to get a better knowledge of this intention. The work is specifically centred on products related to the gastronomy of a particular place. Through a sample of 154 tourists who visited this destination, we sought to know these products’ degree of acceptation. Via structural equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Expressly, the consumers; who had knowledge of the products, recognized that they were made aboard with good quality production; would be satisfied resulting in the purchase intention on those products (Bhakar et al, 2013). This was consistent with Ghalandari & Norouzi (2012); Berbel-Pineda et al, (2018) mentioning that the effect of country-of-origin influenced the willingness to purchase of the consumer. The consumer with low product knowledge had a lower willingness to purchase the product from a foreign country.…”
Section: The Relationship Country Of Origin (Coo) and Purchase Intention (Pi)supporting
confidence: 91%
See 2 more Smart Citations
“…Expressly, the consumers; who had knowledge of the products, recognized that they were made aboard with good quality production; would be satisfied resulting in the purchase intention on those products (Bhakar et al, 2013). This was consistent with Ghalandari & Norouzi (2012); Berbel-Pineda et al, (2018) mentioning that the effect of country-of-origin influenced the willingness to purchase of the consumer. The consumer with low product knowledge had a lower willingness to purchase the product from a foreign country.…”
Section: The Relationship Country Of Origin (Coo) and Purchase Intention (Pi)supporting
confidence: 91%
“…Most of the consumers purchased the well-perceived and good brand imaged products because the positive brand image affected the lower perceived risks (Simonian et al, 2012). Moreover, Wang & Tsai (2014); Berbel-Pineda et al, (2018) found that the brand image increased the consumer's purchase intention. While the findings of Wiyadi & Ayunintyas (2019) research showed that customers who had a positive image of a brand intending purchase of the product.…”
Section: The Relationship Between Brand Image (Bi) and Purchase Intention (Pi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Le et al (2017) explored the relationship between country of origin image and consumers’ purchase behavior and proved that country of origin image has a significant impact on consumers’ perception of product quality, brand attitude, and purchase intention. Berbel-Pineda et al (2018) found that country of origin image affects not only consumers’ perspective on product quality but also their purchase behavior. Samiee (2019) showed that Asian consumers are increasingly shifting from global brands to domestic brands.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Specifically, the “made in” effect, a favourable perception of the country of origin, and the gastronomic culture have a direct relation with the consumer's shopping intentions. The researchers relied on the following literature in writing the research [1] , [2] , [3] , [4] , [5] .…”
Section: Data Descriptionmentioning
confidence: 99%